Personal and general belief in a just world as judgment norms - Alves, H. (2014)
Research on the belief in a just world (BJW) has focused on its intra-individual functions (e.g., psychological well-being) and its inter-individual consequences (e.g., derogation of victims). Recent theorizing, however, has indicated that the BJW may also have more societal functions and consequences, serving as a legitimizing device of the status quo. The studies in the current paper focus on this latter view and are based on Alves and Correia's (2008) research which found that the expression of high personal and general belief in a just world is injunctively normative. Two experimental studies aimed at ascertaining three issues: (1) the dimension(s) of social value (social utility and/or social desirability) on which the BJW normativity anchors; (2) whether the expression of moderate BJW is also injunctively normative; and (3) whether the injunctive normativity of the BJW is related to perceptions of truth. Results indicate that moderate and high personal and general BJW are normative. Yet, whereas the normativity of personal BJW anchors both on social utility and social desirability, that of general BJW anchors only on social utility. We discuss personal and general BJW as judgement norms, whose normativity may not be personally acknowledged (in the case of general BJW) and does not necessarily derive from being perceived as true, but from the fact that such norms carry social value at least in individualistic societies.